Assemblage of Insects on Medicinal Plants: An Insight from ICIMOD Herbal Garden in Godavari of Lalitpur, Nepal - Bhusal, Daya Ram; Shrestha, Sweta; Ghimire, Kishor Chandra (Journal of Institute of Science and Technology, 2019)
Present study was conducted within the herbal garden of International Centre for Integrated Mountain Development (ICIMOD) in Godawari of Kathmandu valley to explore the insect communities in medicinal plants. Five medicinal plants, viz. Rauvolfia serpentina (= Sarpagandha), Urtica dioca (= Sissnu), Zanthoxylum armatum (= Timur), Valeriana jatamansii (= Sungandhawal) and Mentha spicata (= Pudina) were selected for the study. Insects were randomly sampled during four seasons from September 2017 to June 2018 using different collecting techniques, like hand picking, pit-fall traps, net-sweeping and stem beating. A total of 869 insects individuals belonging to 42 different genera were collected and identified. It was found that the abundance of insects was high during spring season (299 insects comprising 35 % of collected species), followed by summer (255 insects comprising 29 % of collected species) and winter (219 insects comprising 25 % of collected species) seasons, and low during autumn season (96 insects comprising 11 % of collected species). It was further found that the abundance of insect species was temperature-dependent, but was independent of relative humidity. The maximum indicator species were present on M. spicata. Taxonomic distinctness (delta+) of insects was high on V. jatamansii, but low on U. dioca.